Introducción a los supermercados de la ciudad de Guayaquil de carritos de compra con lector de barras incorporado que otorgan información de precios y ubicación de los productos mediante pantalla lcd - Aguirre Ubilla, Sulay Alexandra (2009)
This investigation seeks ways to improve the communication with the customer through the installation of information ports, which are operated through a “touch screen” incorporated to shopping carts, facilitating the obtaining of product information such as price, offers, location, details, etc. This system decreases the probability of price marking errors and offers a better service, turning shopping into a pleasant experience. The system allows the supermarkets to satisfy the expectations of the customers. They also will have the benefit of obtaining information about every purchase done with the shopping cart, in order to obtain data related to replacement, supplying and logistic.